Applicative Arabic Language Learning Media: Innovations for Arabic Language Education Lecturers in Higher Education - Huda, Moh Nurul; Munir, Misbahul; Salsabila, Salsabila; Alsaied, Mohamad Abdullah (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2023)
This research aims to analyze the use and innovation of application-based Arabic learning media that Arabic language education lecturers in universities have carried out. This research uses a qualitative approach using observation, interview, and documentation data collection techniques. In contrast, the data analysis technique uses Miles and Huberman, which has three stages: data reduction, data presentation, and conclusion. The research results are first; most Arabic language education lecturers in universities use several platforms in teaching and learning activities such as E-learning Moodle, Google Classroom, Zoom Meeting, Google Meet, and WhatsApp Group. Meanwhile, Arabic Language Education lecturers at universities also make learning videos to make it easier to explain the material, which is then uploaded to YouTube. Second; Innovations developed by Arabic language education lecturers at universities include hyperlink-based LMS At-Talkhis, creating Powerpoint and Camtasia-based Learning Videos, creating Animation-based Learning Videos, and developing Evaluation Media based on Google Forms, Kahoot, and Quizizz.